An Interdisciplinary Perspective on the Relationship between Ethics and Today’s Capitalism - Comsa, Petre; Munteanu, Costea (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper begins by emphasizing the fact that, on a historical scale, one can have several views of the relationship that has existed over time between ethics and capitalism, namely: missionary, ‘Nietzschean’, critical, and ‘regulatory’. It is argued that, nowadays, the capitalization of the contributions supplied, over time, by the four views embraces the form of two modern diametrically opposed perspectives, i.e.: on the one hand, there is the interpretation given by the neo-classical school of thought (mainstream economics) and, on the other hand, it comes to the interpretation given by the Austrian praxeological economic school (libertarian economics). The emphasis of the analysis is put on the assertions developed by the last one, libertarian thinking, that insists on the necessity to operate with a well-defined distinction between the legal level of the matter, the ethical level and the moral one. At the core of the libertarian analysis there is the understanding of the capitalist system being naturally impregnated by ethical values. And this intrinsic ethical nature of capitalism is organically bound to the sphere of the ownership-type relationship. In line with the understanding of the economic system, based on the institutions of the free market as representing ethical capitalism per se, the paper argues that the realities of the world today show governmental interventionism as a main factor that supports non-ethical economic behaviour. As a consequence, the more limited government intervention is, the greater the chance of ethical capitalism, that is, voluntary, non-conflictual and non-aggressive economic market relationships. Under such conditions, a ‘minimal state’ institutional arrangement (that is, the legitimate use of power by the state is limited to preventing fraud or the use of force; it does not include the power to tax or to confiscate property) is the basic condition for the existence of an ethical capitalism that works, which is to say that the chance of an economic system based on ethical values stands in people’s willingness to be part of such an evolution in society that aims to minimise the role of the state. Further, the paper argues that any historical analysis on how societies asserted such a willingness outlines the expression of a secular and unshaken option for growing rather than diminishing state involvement in the economy. It is about people’s perennial preference for the state, namely for the organization of society based on state interventionism (respectively, their preference for the coercive order imposed by the state authorities, order based, through its own nature, on the subjugation of private property and the aggression against individual freedom), with a preference for the government intervention over the organization of a society based on free market functioning (which is equivalent, in fact, to their rejection of a voluntarily and spontaneously non-violent order, based on the observance of private property and individual freedom, brought about by the free functioning of markets). In the last part of the paper there are put forward for discussion the possible explanations for this perennial preference for non-ethical capitalism, the analysis focusing on two directions: firstly, on that of social ontology; and then, on that of human psychology.